выражение 2sin(pi/2+a)*cos(2pi+a)+cos(3pi/2-a)*sin(a-3pi)+sin^2

yulya158 yulya158    2   27.09.2019 02:00    0

Ответы
makar32ryc makar32ryc  08.10.2020 21:41

Полагаю, что в последнем потеряно альфа.


2\sin(\frac{\pi}{2} +\alpha )\cos(2\pi +\alpha )+\cos(\frac{3\pi}{2} - \alpha )\sin(\alpha -3\pi )+\sin^2\alpha =\\ \\ =2\cos\alpha \cos\alpha +(-\sin\alpha )(-\sin \alpha )+\sin^2\alpha =2\cos^2\alpha +\sin^2\alpha +\sin^2\alpha =\\ \\ =2\cos^2\alpha +2\sin^2\alpha =2(\underbrace{\cos^2\alpha +\sin^2\alpha }_{=1})=2\cdot 1=2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра